Carnitine in Valproate-Induced Hyperammonemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effect of carnitine supplementation in valproic acid (VPA) treated patients presenting with hyperammonemia was investigated in 69 children and young adults seen at the Zentrum der Kinderheilkunde, Goethe-Universitat Frankfurt, and Universitat Erlanger, FRG.